Comparison of the impact of open and laparoscopic inguinal hernia operations on male sexual function and pain during sexual activity. (24th September 2021) - Aykanat, Ibrahim C.; Er, Sadettin; Senel, Cagdas; Comcali, Bulent; Aslan, Yilmaz; Balci, Melih; Yuksel, Bulent C.; Tuncel, Altug
Abstract: In the current study, we aimed to compare sexual function and pain during the sexual activity of men who underwent surgery with the open or laparoscopic total extraperitoneal hernia repair techniques. Patients were randomised into two groups according to the technique used during the operation: the Lichtenstein hernia repair open technique ( n = 63) and the laparoscopic total extraperitoneal repair technique ( n = 57). In both groups, postoperative sexual function score was significantly improved compared with the preoperative period ( p < .001 for both), but the change was higher in the laparoscopy group (6.8 ± 3.7) compared with the open group (4.3 ± 4.4) ( p < .001). In both groups, postoperative pain during sexual activity score was significantly decreased compared with the preoperative period ( p = .001 for the open group and p < .001 for the laparoscopy group), with the amount of decrease being higher in the laparoscopy group (1.8 ± 0.9) compared with the other (1.1 ± 1.4) ( p = .002). This study showed that both hernia repair techniques had a positive impact on sexual function and pain during sexual activity. The improvement in sexual parameters and pain during sexual intercourse was better in the laparoscopy group.